Invigorating Knowledge Sharing in Higher Education : Indian Initiatives - Arun Kumar, A.; Shekhar, Vedulla (Prabandhan: Indian Journal of Management, 2017)
Higher education institutions are temples of learning and repositories of knowledge. These are the educational hotspots which are highly responsible for knowledge creation, information storage, knowledge sharing, learning, and reuse. Knowledge has a high impetus in higher education. Knowledge management is not a new phenomenon in higher education. In the Indian higher education system, knowledge sharing plays a vital role. Knowledge sharing is involved in administrative and academic activities in higher educational institutions like colleges and universities. However, a lacuna still persists ; a gap in knowledge sharing still exists among researchers and academicians in the higher educational institutions. To fill this gap and to motivate stakeholders of higher education to share knowledge to promote their research, the Government of India has introduced several initiatives. These initiatives invigorate the researchers and academicians to add to the knowledge base of higher education and share knowledge among peer groups. This paper emphasized on the importance and benefits of knowledge sharing practices in higher education in the Indian perspective. The paper also threw some light on some of the initiatives taken up by the Government of India in promoting knowledge sharing among higher educational stakeholders.